WATER TREATMENT SYSTEM UNTUK PENINGKATAN MUTU KUALITAS AIR KOLAM AKIBAT PERTUMBUHAN ALGA (ALGAE) - Devi Megarusti Pratiwi; Mitsaq Addina Nisa; Rafie Itharani Ulkhaq (Politeknik Negeri Semarang, 2025)
One of the areas planned as a swimming pool tourist attraction with natural views is located in Cipelang Village, Cijeruk District, Bogor Regency, which has a land area of 1.5 hectares. The purpose and contribution of the research is to plan a swimming pool system (water treatment) in a tourist pool contaminated by algae bloom. This research will begin by calculating the amount of rainwater discharge and water load on the ground surface, then measuring the water quality of the swimming pool contaminated with algae bloom in accordance with the Minister of Health Regulation Number 2 of 2023, namely Temperature, Turbidity, Odor, Laboratory Acidity Degree (pH), Residual Chlorine, Escherichia Coli. Then continued by compiling a DED (Detail Engineering Design) for the pool structure along with its water treatment. The results of water quality testing for the swimming pool are for parameters Temperature 26°C, Turbidity 0.45 NTU, Odor 1.4, Laboratory Acidity Degree (pH) 5.7, Residual Chlorine 1.75 mg/L, Escherichia Coli <1 CFU/100ml. After being designed for a pump system and implementing a water treatment system in the filtration system and adding PAC (Poly Aluminum Chloride), Alum, Soda Ash Dense USA, and 60% Chlorine Powder chemicals, the results of laboratory tests after the water was clear were that it met the requirements for all parameters.